ACTUAL PROBLEMS OF STATE FINANCING IN THE CONTEXT OF IMPLEMENTATION OF PARTNER INFRASTRUCTURE PROJECTS OF THE STATE AND BUSINESS - SHULIUK, Bohdana (Scientific journal «World of Finance», 2021)
Introduction. An integral condition for the efficient functioning of the economy is the constructive financial interaction between the state and business. Such cooperation is due to the need to improve the infrastructure sectors, the efficiency of which affects not only the welfare and quality of life, but also creates the conditions for intensifying investment activities and increasing productivity in the fields of material production. However, modernization of infrastructure is not possible only at the expense of private partners, so it requires financial participation of state or local authorities. The purpose of the article is to identify the problems of public funding of public-private partnership infrastructure projects in Ukraine and to develop recommendations for their solution, taking into account the best world practices. Results. The study showed that public funding of public-private partnership projects in Ukraine is carried out through the use of direct and indirect state support. It is established that its forms are insufficiently adapted in domestic practice, as they have a restrictive nature of action, and also contain many gaps in the legislation. Conclusions. Increasing the investment attractiveness of infrastructure projects implemented on the basis of public-private partnership requires state support. At the same time, state and local authorities should adhere to the provisions: providing state support in the process of implementing strategically important PPP projects in the field of socio-economic activities by legislative regulation of the procedure for determining the level of contribution of a supported investment project; determining the type of financial participation of the state (provision of state guarantees, subsidies or budget investments) should be based on economically justified performance indicators; involvement of state representatives to assess the feasibility of choosing certain forms of state support, forecasting the possible risks to prevent budget imbalances; ensuring transparency of public funding of PPP projects, which will increase the level of confidence in the investment market.